First-Line Chemotherapy with Liposomal Doxorubicin Plus Cyclofosfamide in Metastatic Breast Cancer: A Case Report of Early and Prolonged Response. (July 2013) - Riccardi, F.; Mocerino, C.; Barbato, C.; Ambrosio, F.; Festino, L.; Vitale, M.G.; Carrillo, G.; Trunfio, M.; Minelli, S.; Cartenì, G.
The treatment choice for metastatic breast cancer should consider the appropriate balance between efficacy and toxicity of the therapy. We discuss a clinical case with an early response and prolonged to liposomal anthracyclines-based chemotherapy, without cardiotoxicity, enhancing the evidence of safety of liposomal formulation to prevent heart damage. Moreover, the case seems to be of interest for the role of 18 F-FDG-PET in clinical response assessment: an early decrease of the standardized uptake value value, even before conventional imaging evaluation, is highly predictive for prolonged clinical response.